2018
DOI: 10.1038/s41416-018-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

S100B and LDH as early prognostic markers for response and overall survival in melanoma patients treated with anti-PD-1 or combined anti-PD-1 plus anti-CTLA-4 antibodies

Abstract: S100B could serve as a strong baseline marker for OS in melanoma patients receiving anti-PD-1 therapy. Rising S100B levels during the first weeks of therapy could help guide treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 42 publications
5
78
0
Order By: Relevance
“…Not only baseline LDH levels, but also the changes in LDH levels during the first weeks of checkpoint inhibition appear to relate with treatment outcomes. [56][57][58] A retrospective study in 238 melanoma patients showed that patients responding to pembrolizumab had a marked reduction in LDH levels after 6 weeks of treatment (median: −15.6%; ICR: −23.1% to −1.3%), whereas LDH levels increased in patients with progressive disease (median: + 6.2%, ICR: −12.8% to +44.5%) (p = .0088). Increases in LDH levels of 25% or more were strongly associated with a detrimental OS (HR 10.75; 95% CI 4.62-25.02).…”
Section: On-treatment Ldh Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only baseline LDH levels, but also the changes in LDH levels during the first weeks of checkpoint inhibition appear to relate with treatment outcomes. [56][57][58] A retrospective study in 238 melanoma patients showed that patients responding to pembrolizumab had a marked reduction in LDH levels after 6 weeks of treatment (median: −15.6%; ICR: −23.1% to −1.3%), whereas LDH levels increased in patients with progressive disease (median: + 6.2%, ICR: −12.8% to +44.5%) (p = .0088). Increases in LDH levels of 25% or more were strongly associated with a detrimental OS (HR 10.75; 95% CI 4.62-25.02).…”
Section: On-treatment Ldh Levelsmentioning
confidence: 99%
“…However, the differences were less pronounced, possibly due to a high incidence of immune-related adverse events in these patients, which can also elevate LDH levels. 57 At the Radboudumc, we assessed the changes in LDH levels in 58 bladder cancer patients treated with anti-PD-(L)1. Here, we also identified a decline in LDH levels in responding patients after two cycles (median: −10,9%, ICR: −21,4% to +1,1%), whereas LDH levels increased in non-responders (median: +5,1%, ICR: −2,9% to +18,0%) (p = 0,003) [unpublished data].…”
Section: On-treatment Ldh Levelsmentioning
confidence: 99%
“…The percentage of patients that had elevated LDH is similar in both reports (32% in our cohort vs. 36% in the CheckMate 067 trial). In the CheckMate 067 trial, the S100B levels, which are a known prognostic factor [38,39], were not reported; in our study, 44% of the patients had elevated S100B. Together, these aspects define a collective of patients that probably had a worse prognosis compared to the patients included in the clinical trial.…”
Section: Discussionmentioning
confidence: 45%
“…25 Furthermore, baseline LDH was significantly associated with an impaired overall survival in metastatic melanoma patients treated with combination anti-CTLA-4 and anti-PD-1. 1 , 26,27 These findings highlight the need for assessment of immune parameters along with clinical and histopathologic factors for the administration of personalized therapies for patients with metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%